Perceptions and Practices of English and Nepali Medium Instruction - Khadka, Bishnu Kumar (Journal of Educational Research and Innovation, 2024)
This study aimed to explore the perceptions and practices of key stakeholders—students, teachers, school management committee (SMC) chairs, and parents—regarding the use of Nepali Medium Instruction (NMI) and English Medium Instruction (EMI) in government-funded community schools. A quantitative research design was employed, with a structured questionnaire distributed to 200 participants, including students (N = 100), teachers (N = 50), SMC chairs (N = 20), and parents (N = 30) from four government-funded community schools across Nepal. The schools were selected through purposive sampling to ensure representation from both NMI- and EMI-based instruction. The study findings revealed a strong parental preference for English Medium Instruction (EMI), with 70% of parents considering it important or very important. However, teachers expressed a more balanced view, with 70% recognizing the significance of Nepali Medium Instruction (NMI) and 68% acknowledging the importance of EMI. Teachers perceived EMI as beneficial for improving students' English language proficiency (48%) and enhancing career prospects, while also noting that NMI fosters a better understanding of academic concepts (58%) due to language familiarity. Both parents and teachers observed that EMI can hinder students' confidence, with 32% of parents and 37% of teachers reporting that language barriers in EMI reduce students' self-esteem and classroom participation. Additionally, limited access to educational resources in Nepali was highlighted by 33% of parents and 35% of students. While the highest percentage of teachers (40%) and students (47%) preferred NMI, a majority of parents (52%) favored EMI. The findings contribute to the ongoing discussion on the medium of instruction in Nepal’s education system, particularly regarding the balance between preserving cultural identity and improving future educational and career opportunities for students.